"Cute Goddess is Actually an Aunty": The Evasive Middle-Aged Woman Streamer and Normative Performances of Femininity in Video Game Streaming. (July 2022) - Ruotsalainen, Maria
In this paper the focus is on the representations of "middle-aged" or "aging" women streamers in western media. I analyze discussions in Western online media around a case of Chinese DouYu live-streamer. "Qiaobiluo Dianxia, " as her streamer name goes, became a topic in Western media after a glitch in her live stream revealed her to be a middle-aged woman, rather than young woman she was assumed to be. The discussions are analyzed with critical discourse analysis. It is argued that the aging bodies of women, both their presence and absence, should be read and understood through toxic gaming culture and geek masculinity and the hegemonic discourse they constitute.